Water and Watershed Management - Das, B. L. (Indian Forester, 1964)
As a country progresses in its industrial development, its water requirement increases very rapidly. Sound watershed management aims at increasing the usable water yield. In this article, some of the principles of water yield control have been discussed and attention has been focussed on the hydrological role of vegetation on prevention of flood flows.